Targeted Therapy for CML Patients on Imatinib: Role of Novel Variants of Human Organic Cationic Transporter 1 (hOCT1) - Bhutani, Namrata; Naaz, Huda; Anbhule, Amol Parshuram; Kaur, Inderpreet; Singh, Tejinder; Kaur, Jaswant (Disease and Health Research: New Insights Vol. 3, 2024)
SLC22A1 is the gene responsible for encoding Human Organic Cationic Transporter 1 (hOCT1), which is among a group of three similar transporters facilitating the uptake of numerous organic cations from the bloodstream into epithelial cells. hOCT1 shows a tendency towards several natural substances like dopamine, along with some medications like metformin, cimetidine, imatinib, etc. The expression of the hOCT1 gene is a reliable indicator of treatment response and clinical outcomes in patients before starting therapy. Furthermore, the expression of the hOCT1 gene has been known to influence the efficacy of imatinib therapy, with higher expression levels correlating with improved hematological and molecular responses. This chapter proposes that evaluating the expression levels of the hOCT1 gene can be a useful method for predicting the effectiveness of imatinib treatment in recently diagnosed chronic myeloid leukemia (CML) patients. Understanding the expression patterns and polymorphisms of the hOCT1 gene could thus inform the design of personalized therapeutic strategies tailored to individual patients at diagnosis. This knowledge could potentially optimize treatment outcomes and enhance the overall management of CML patients undergoing imatinib therapy.